A new species of Commelina (Commelinaceae) from India. Issue 2 (3rd July 2018) - Nandikar, Mayur D.; Gurav, Rajaram V.
ABSTRACT: The present article describes and illustrates a new species of Commelina from dryland hillocks of Karnataka, India. The new species Commelina rupestris shares morphological similarities with C. badamica, C. hirsuta and C. attenuata, but differs in its perennial habit, knotted rhizomatous, definite base, broadly elongate, thickened tuberous roots, characteristically ligulate, linear to lanceolate leaves, minutely fused spathes, one- to two-seeded bilocular capsules, and stramineous to light brown, rostrate seeds.